2020
DOI: 10.1103/physrevd.101.033001
|View full text |Cite
|
Sign up to set email alerts
|

Weak structure functions in νlN and νlA

Abstract: We study the effect of various perturbative and nonperturbative QCD corrections on the free nucleon structure functions (F W I iN (x, Q 2 ); i = 1 − 3) and their implications in the determination of nuclear structure functions. The evaluation of the nucleon structure functions has been performed by using the MMHT 2014 PDFs parameterization, and the TMC and HT effects are incorporated following the works of Schienbein et al. and Dasgupta et al., respectively. These nucleon structure functions are taken as input… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 88 publications
(205 reference statements)
0
32
0
Order By: Relevance
“…For the evaluation of the weak nuclear structure functions not much theoretical efforts have been made except that of Kulagin et al [40,41] and Athar et al (Aligarh-Valencia group) [30][31][32][33][34][35][36][37][38][39]. Aligarh-Valencia group has studied nuclear medium effects in the structure functions in a microscopic model which uses relativistic nucleon spectral function to describe the target nucleon momentum distribution incorporating the effects of Fermi motion, binding energy and nucleon correlations in a field theoretical model.…”
Section: Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…For the evaluation of the weak nuclear structure functions not much theoretical efforts have been made except that of Kulagin et al [40,41] and Athar et al (Aligarh-Valencia group) [30][31][32][33][34][35][36][37][38][39]. Aligarh-Valencia group has studied nuclear medium effects in the structure functions in a microscopic model which uses relativistic nucleon spectral function to describe the target nucleon momentum distribution incorporating the effects of Fermi motion, binding energy and nucleon correlations in a field theoretical model.…”
Section: Formalismmentioning
confidence: 99%
“…W 6A (ν A , Q 2 ) does not contribute to the cross section as it vanishes when contracted with the leptonic tensor L µν . The nuclear structure functions W iA (ν A , Q 2 ) (i = 1 − 5) are written in terms of the dimensionless nuclear structure functions F iA (x A ); (i = 1 − 5) as [39,45]:…”
Section: Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…. It has been shown that weak interaction CC structure functions F ν,CC 1 and F ν,CC 2 at NLO with TMC and higher-twist corrections have only small differences (< 1%) from the same structure functions evaluated at NNLO with TMC, without additional higher twist corrections, though somewhat large differences arise for F ν,CC 3 (e.g., an 8% correction for Q 2 = 1.8 GeV 2 and x = 0.225) [100]. We have not considered dynamical higher twists in our discussion here.…”
mentioning
confidence: 93%
“…Finally, we note that modeling nuclear corrections to structure functions is much more complex in this regime [100,[117][118][119][120] and may be different for electromagnetic and weak scattering. The MINERvA experiment [121] measurements of neutrino DIS scattering on multiple nuclear targets shows what can be interpreted as the onset of nuclear shadowing in the axial-vector current.…”
mentioning
confidence: 99%